2010
DOI: 10.1057/biosoc.2009.3
|View full text |Cite
|
Sign up to set email alerts
|

The NIDA brain disease paradigm: History, resistance and spinoffs

Abstract: This article examines 'the NIDA paradigm', the theory that addiction is a chronic, relapsing brain disease characterized by loss of control over drug taking. I critically review the official history of the National Institute on Drug Abuse (NIDA) paradigm and analyze the sources of resistance to it. I argue that, even though the theory remains contested, it has yielded important insights in other fields, including my own discipline of history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 10 publications
2
83
0
Order By: Relevance
“…Nutt, 2009). We agree with Courtwright (2010) that those of more conservative views regarding addiction neuroscience see it as strengthening the case for the status quo, or possibly justifying even more punitive policies in order to prevent an epidemic of an acquired 'brain disease'.…”
Section: Compulsory Addiction Treatment For Paternalistic Reasonssupporting
confidence: 62%
See 1 more Smart Citation
“…Nutt, 2009). We agree with Courtwright (2010) that those of more conservative views regarding addiction neuroscience see it as strengthening the case for the status quo, or possibly justifying even more punitive policies in order to prevent an epidemic of an acquired 'brain disease'.…”
Section: Compulsory Addiction Treatment For Paternalistic Reasonssupporting
confidence: 62%
“…Indeed, chronicity was the major reason for the hypothesis that addiction was a brain disease in the late nineteenth century (Courtwright, 2010). Physicians who treated alcoholism and opiate dependence in the second half of the nineteenth century reported that their patients often returned to alcohol and opiate use after lengthy periods of abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…M a n u s c r i p t 3 A growing literature has begun to examine the extent to which neuroscientific explanations of addiction have influenced the views of addiction held by the general public, addiction clinicians and neuroscientists, and addicted persons Dingel, et al, 2011;Hammer, Dingel, Ostergren, Nowakowski, & Koenig, 2012;Hammer, et al, 2013;Meurk, Hall, Morphett, Carter, & Lucke, 2013;Meurk, Partridge, et al, 2014;Netherland, 2011). Although there are some who express concerns about the negative consequences of the BDMA (Hammer, et al, 2013), others suggest that the predicted positive and negative social impacts of the BDMA have been overstated (Courtwright, 2010). Although some aspects of brain-based explanations of addiction are accepted by most people (Meurk, Hall, Morphett, Carter, & Lucke, 2013), these ideas tend to be incorporated into older ideas about addiction, often in idiosyncratic ways.…”
Section: Introductionmentioning
confidence: 99%
“…Across the 1980s and 1990s this research came to focus increasingly heavily on neuroscientific methods and frameworks. In so doing, new biological truths about the brain -about neurotransmitters and receptor sites for drugs -were created (Vrecko, 2010;Courtwright, 2010). At the same time, the advent of new imaging technologies enabled cheaper and easier study of the brain, without the need for surgical access to human brain tissue (Campbell, 2007).…”
Section: The Rise Of the Neuroscience Of Addictionmentioning
confidence: 99%
“…As historian David Courtwright (2010) points out, although the brain model has achieved cultural prominence as a scientific theory, its clinical influence has so far been limited, and cannot be said to have impacted, as neuroscientists promised, on the stigmatisation of addicts or on prohibitionist drug policy in the United States. Despite these limitations, neuroscience continues to expand into the domain of addiction and compulsive behaviour, taking in socalled behavioural addictions and those that defy strict classification, such as overeating and obesity.…”
Section: The Rise Of the Neuroscience Of Addictionmentioning
confidence: 99%